Fewer non‐native insects in freshwater than in terrestrial habitats across continents. (9th September 2022) - Sendek, Agnieszka; Baity‐Jesi, Marco; Altermatt, Florian; Bader, Martin K.‐F.; Liebhold, Andrew M.; Turner, Rebecca M.; Roques, Alain; Seebens, Hanno; Spaak, Piet; Vorburger, Christoph; Brockerhoff, Eckehard G.
Abstract: Aim: Biological invasions are a major threat to biodiversity in aquatic and terrestrial habitats. Insects represent an important group of species in freshwater and terrestrial habitats, and they constitute a large proportion of non‐native species. However, while many non‐native insects are known from terrestrial ecosystems, they appear to be less represented in freshwater habitats. Comparisons between freshwater and terrestrial habitats of invader richness relative to native species richness are scarce, which hinders syntheses of invasion processes. Here, we used data from three regions on different continents to determine whether non‐native insects are indeed under‐represented in freshwater compared with terrestrial assemblages. Location: Europe, North America, New Zealand. Methods: We compiled a comprehensive inventory of native and non‐native insect species established in freshwater and terrestrial habitats of the three study regions. We then contrasted the richness of non‐native and native species among freshwater and terrestrial insects for all insect orders in each region. Using binomial regression, we analysed the proportions of non‐native species in freshwater and terrestrial habitats. Marine insect species were excluded from our analysis, and insects in low‐salinity brackish water were considered as freshwater insects. Results: In most insect orders living in freshwater, non‐native species were under‐represented, while they were over‐represented in a number of terrestrial orders. This pattern occurred in purely aquatic orders and in orders with both freshwater and terrestrial species. Overall, the proportion of non‐native species was significantly lower in freshwater than in terrestrial species. Main conclusions: Despite the numerical and ecological importance of insects among all non‐native species, non‐native insect species are surprisingly rare in freshwater habitats. This is consistent across the three investigated regions. We review hypotheses concerning species traits and invasion pathways that are most likely to explain these patterns. Our findings contribute to a growing appreciation of drivers and impacts of biological invasions.